Emotional quotient and personality traits of guidance counselors - Diokno, Olivia L.; De Guzman, Leticia S.; Ganaden, Mildred S.; Marcelo, Editha M. (2007)
The study aimed to know the emotional quotient and personality profile of the guidance counselors of the different private schools of Lipa City, Batangas. The respondents were Guidance Counselors or administrators of the private schools offering pre-elementary, elementary, secondary, and tertiary education in the Division of Lipa. The review of literature discussed the theory of Dr. Reuben Bar-on on Emotional Quotient and the importance of EQ to the personal and professional life of Guidance Counselors. The research also dealt on the personality profile of the counselors using Gordon Personal Profile and Gordon Personal Inventory.
"March 2007."
Thesis (M.A. Guidance)--University of the Philippines Diliman.
Keywords: Student counselors -- Philippines -- Lipa City (Batangas) -- Psychology; Emotional intelligence; Personality